ANALISIS PARTISIPASI PETERNAK DALAM PEMBIBITAN KERBAU MOA DI PULAU MOA KABUPATEN MALUKU BARAT DAYA - Rajab Rajab; Michel J. Matatula; Elisabet L. Slubyanik (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
A success of government effort to support a breeding development program of local livestock not get out of the participation of breeder society. The research objective was to analysis local breeder knowledge and participation rate and their both correlation in Moa buffalo breeding in Moa island. This research was conducted by using survey method, with 30 respondents from three village in which ten for each village were selected to interview. Data collected was analysed by using descriptive method. Observed variables were knowledge and participation rate of local buffalo herders. The results showed that knowledge scores of the breeders from the three villages Tounwawan, Klis and Werwaru were 15,0 ; 15,8 and 15,8 respectively and categorized in low level. The participation scores of local buffalo breeder were 26,9 (high), 17,5 (low), and 20,4 (medium) respectively for Tounwawan, Klis and Werwaru. There was no correlation of the rate of breeders knowledge and their participation scores in breeding development of Moa buffalo in Moa island.